Does sentinel lymph node biopsy not reduce a chance to cure breast cancer patients? - Pluta, Piotr; Piekarski, Janusz; Nejc, Dariusz; Jeziorski, Arkadiusz (Contemporary Oncology/Współczesna Onkologia, 2004)
Sentinel lymph node biopsy (SLNB) is a technique gaining popularity in the treatment of breast cancer patients. This procedure allows to avoid performing elective axillary dissection (AD) in a specified group of patients, which has an important implication for reducing morbidity. Nevertheless, the decision of abandonment AD in sentinel lymph node negative patients raises some concerns about compromising the chances of cure in this group of patients. This review examines data regarding axillary recurrences after SLNB without AD. Clinical trials showed that during follow-ups ranging from 24 to 46 months, axillary recurrence developed in 0 to 1.4% of patients after SLNB alone, and these data are similar to outcomes after AD. We were concerned with the implications of false-negative biopsies for adjuvant treatment. Nano et al demonstrated that owing to a false-negative SLNB, only 0.7% of patients in that study would not have received adjuvant systemic therapy, which could have potentially jeopardized their survival prospects. We also looked through the randomized trials comparing SLNB alone with AD. In the randomized trial conducted by Veronesi et al there were no significant differences between SLNB-alone group and AD group in the rate of unfavorable events and deaths during 46 months of follow-up. However, before large clinical randomized trials concerning different aspects of sentinel lymph node biopsy are finalized, we are not able to provide a complete answer to the title question.